Revealing the Cause of Selling Protected Animals in Gorontalo in View from a Criminological Perspective - Fadlan Iswahyudi Tobuhu (Estudiante Law Journal, 2022)
Abstract: The purpose of the study is to find out and analyze through a Criminology review what factors cause the occurrence of the Crime of Selling Protected Wildlife in Gorontalo. The type of research used is Empirical research and uses Qualitative analysis techniques.  The results of this study show that the sale of protected wildlife in Gorontalo is caused by several factors including, economic factors, environmental factors, and educational factors.  Upaya prevention carried out so that the community is not involved in buying and selling protected wildlife includes, Preventive Efforts made employing Obstruction on transportation routes, and conducting forest patrols, the community is required to report if they see a criminal act of buying and selling wildlife, and conducting education. Repressive efforts, the enforcement efforts carried out by Gakkum himself are to hand over the perpetrators to the Police.